Visão baseada em recursos numa associação de catadores no Oeste Potiguar - Gomes, Abigail Jéssica da Silva Araújo (Universidade Federal Rural do Semi-Árido, 2015)
The rapid changes that occur in the competitive environment of organizations make the chosen strategies to be crucial in its maintenance in the market. This ambience is not only faced by organizations that seek profit, but it is the reality of many social organizations that have public purposes and need to adopt strategies in their day to day to survive. Despite having social purposes, the public interest organizations also need to acquire its resources on private means, oftentimes competing with private and public companies to stay in the market. The present paper has as the subject of research to know whether OSCIPS (Civil Society Organizations of Public Interest) have analysis structure and decision capable of supporting the implementation of VRIO (Value, Rarity, not Imitability and Organization) model as a strategic management tool in order to improve their possibilities for survival in the market. Therefore, this papaer made use of the Resource Based View, more specifically the VRIO model, derived from the Strategic Management, in order to achieve the objective of analyzing the feasibility of its application in a recycling association in the Potiguar West. To do so a field research was used with qualitative analysis, with data obtained from eight interviews along with stakeholders (manager and associates, municipal government power, recyclable material buyers and competitor) from the collectors association analyzed. The results suggest that the reputational feature allows the association has greater visibility in the city. However, although it is an important achievement, it does not allow the organization to overcome the main weaknesses encountered that refer to the financial, human, technologicals and physical resources. There is demotivation of members due to the lack of transparency with the financial management, lack of punishment with uncommitted collectors and the low pay of collectors. The machines, a technological resource, that value the value of the materials, are not yet in operation. The association's relationship turns out to be friendly with the community, conflicted with the city hall and unstable with the majority of buyers, because there is constancy in the sale of recyclable materials only with one of them. The competitive situation of the surveyed association is on a temporary disadvantage, suggesting that the strategy to be adopted is to invest in the collector's stimulus, to place the machines in operation, thereby improving the compensation and reduction of financial dependence of city hall. It is also suggested that seeks a better relationship with its stakeholders, especially the city hall, since it largely funds its activities in order to enable its survival in the long run. The association has a similar vision with the one from the stakeholders, suggesting that it is able to make a coherent environmental analysis with its reality. However, it is not positioned strategically, seeking solutions from the demands that arise on a daily basis, meaning, not acting proactively, but reactive
View based on resources in a collectors association in the Potiguar West
Keywords: Strategic management; Competitive advantage; Stakeholders; Social organizations; Collectors association - West Potiguar; Gestão estratégica; Vantagem Competitiva; Stakeholders; Organizações Sociais; Associação de catadores - Oeste Potiguar; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE